2021
DOI: 10.1111/jvim.16063
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, recurrence, and outcome of postrace atrial fibrillation in Thoroughbred horses

Abstract: Background: Atrial fibrillation (AF) impacts performance and horse and jockey safety. Understanding the outcomes of AF identified postrace will better inform regulatory policy. Hypothesis/Objectives: To investigate the outcomes after episodes of AF identified postrace and determine whether affected horses are at increased risk of additional episodes compared to the general racing population. Animals: Total of 4684 Thoroughbred racehorses. Methods: Race records for Thoroughbred horses racing in Hong Kong from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 61 publications
(203 reference statements)
3
42
0
Order By: Relevance
“…Both observers were blinded to the results of automated rhythm classification. Previously published criteria 5,13,27 were used determine the rhythm abnormality. Each observer independently classified the heart rhythm as SR, SR with ectopy or AF.…”
Section: Manual Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Both observers were blinded to the results of automated rhythm classification. Previously published criteria 5,13,27 were used determine the rhythm abnormality. Each observer independently classified the heart rhythm as SR, SR with ectopy or AF.…”
Section: Manual Assessmentmentioning
confidence: 99%
“…A trial fibrillation (AF) is the most commonly identified performance limiting arrhythmia in racehorses. [1][2][3][4][5] The estimated frequency of AF occurring after racing varies amongst jurisdictions from 0.2 to 2.7 per 1000 starts. 1,[3][4][5] AF identified after exercise is typically paroxysmal (PAF), converting to sinus rhythm (SR) within 72 h. [1][2][3][4][5][6] In addition to AF, other arrhythmias occurring immediately post exercise can be very short lived and challenging to capture in the absence of wearable technology.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this study Laura Nath and co‐workers in Australia and Hong Kong investigated the outcomes after episodes of atrial fibrillation (AF) identified post‐race and determined whether affected horses are at increased risk of further episodes .…”
Section: Post‐race Atrial Fibrillation In Thoroughbredsmentioning
confidence: 99%